A critical overview of thin films coating technologies for energy applications. Issue 1 (31st December 2023) - Hossain, Mohammad Istiaque; Mansour, Said
Abstract: We report on several state of the art thin films coating technologies including physical vapor deposition (PVD) and solution process deposition techniques. Such techniques have their own significance to develop the energy efficiency devices. Choosing the right technique has become very critical in recent days as the scaling varies significantly with the technology. Thus, it becomes obvious to pick-up the right deposition procedure according to the needs where substrate size, film thickness, and required surface roughness are critically involved. Among all techniques, PVD offers various advantages, which include full control over growth, pristine film quality, large-scale fabrication, stacking of thin films, co-deposition flexibility, and controlling of the deposition temperature. In addition, such techniques can be adapted in small-scale research based labs with capping in terms of budget. Such vapor deposition processes also result in pin-hole free, homogeneous and continuous thin films which are highly desirable parameters for many energy related applications. Solution process techniques such as dip, spin, blade, and roll coating techniques are also discussed to provide an overall view. This report aims to give in-depth cross sectional review of all deposition techniques considering both positive and negative sides. PVD growth processes are very efficient where pattering of films are very significantly required. Hence, in this work, we have captured many deposition techniques where the properties of the films are very crucial to end up with different morphologies. The goal is to compare various techniques as a key parameter to control the fine formation of thin films. We are convinced that our report will show substantial importance to a wider group of materials scientists, chemists, physicists, and to the wider photovoltaic community to pick the best-suited vehicle for thin film growth purposes.